Connecting precipitation inputs and soil flow pathways to stream water in contrasting boreal catchments. Issue 16 (4th September 2014) - Peralta‐Tapia, A.; Sponseller, R. A.; Tetzlaff, D.; Soulsby, C.; Laudon, H.; Bishop, Kevin; Seibert, Jan
Abstract Stable isotopes of water are one of the most widely used tools to track the pathways of precipitation inputs to streams. In the past, soils have often been treated as black‐boxes through which precipitation is routed to streams without much consideration of how, when, and where water is transported along soil and groundwater flow paths. Here, we use time series of stable isotopes (18O) in precipitation, soil/groundwater, and stream water to evaluate how landscape structure and heterogeneity influence seasonal hydrological patterns characteristic of boreal headwater catchments. To do this, we collected water throughout a full year at three adjacent catchments draining forest, mire, and mire/lake ecosystems within the Krycklan Experimental Catchment of northern Sweden. Isotope time series from forest and mire groundwater piezometers showed spatial and temporal heterogeneity in the dominant hydrologic flow pathways connecting precipitation to stream flow at different sites. The isotopic signature of stream water suggested strong connections to the dominant landscape elements within each catchment. These connections translated into greater temporal variability in the isotopic response of streams draining lake and wetland patches, and a much more attenuated pattern in the forest‐dominated catchment. Overall, seasonal changes in the isotopic composition of streams and groundwater illustrate how differences in landscape structure result in variable hydrological patterns in the boreal landscape. Copyright © 2014 John Wiley & Sons, Ltd.